THEORETICAL STUDY of Ag-Ag DISTANCE IN CARBOXILIC DIMERS USED IN THE FORMATION OF NANOSTRUCTURES - Guzmán Duxtan, Aldo (2013)
In this paper we present a quantum theoretical study of the structure and distribution of active sites of various carboxylic silver dimers. The study was done with the sofware Spartan08 and with the calculation program Q-Chem, in order to determine the most appropriate precursor for the synthesis of nanostructures. The calculations were performed on a computer with an Intel Core 2 Quad processor, using the methods of Hartree-Fock and density functional (B3LYP) and using the pseudopotentials of Hay and Wadt (LANL2DZ and LANL1MB). We used carboxylates with electron donors and acceptors to assess their influence on the distance of the metal centers and the distribution and energy of the frontier orbitals. Mapping of the frontier orbitals HOMO and LUMO, performed on a density isosurface under the frozen core approximation, allowed to find the distribution of electrophilic and nucleophilic active sites, respectively. The results indicate that the electrophilic sites of all dimers except silver triyodoacetato are located at the ends of the shaft linking the metal atoms The shortest distance Ag-Ag was determined for the silver pivalate, while the higher reactivity was determined for silver benzoate derivatives precursors, being the 4-hydroxybenzoate and p-chlorobenzoate the most susceptible to an electrophilic or nucleophilic attack, respectively.